Phil Pastras. Dead Man Blues: Jelly Roll Morton Way Out West. Berkeley: University of California Press, 2001. xx, 246 pp. - Ogren, Kathy J. (Current Musicology, 2001)
Author Phil Pastras opens his biographical study of legendary pianist Jelly Roll Morton with an epigram from poet Dylan Thomas-"Oh make me a mask"-and with that signal, Dead Man Blues: Jelly Roll Morton Way Out West takes us on the road with trickster Ferdinand Joseph LaMenthe, a.k.a. Jelly Roll. Pastras appreciates the facility with which Morton, like many Mrican American jazz musicians, used performative masks to strate-gize resilient careers in a capricious music business. Pastras writes: "Morton was a man of many masks, especially at the beginning of his ca-reer: pool hustler, card shark, pimp, vaudevillian, pianist, composer and bandleader. He did not focus exclusively on the music until after his five year stay on the West Coast, from 1917 to 1923" (6). Acknowledging the examples set by Ralph Ellison (1964) and Albert Murray (1976) in their essays on the ritual importance of donning masks in performance, Pastras sets out to find "what the mask tells us about its maker" (12). And the setting for this exploration-the American West-locates Jelly Roll as a rambler who reinvents himself and finds his defining identity on the American frontier.